Interproximal papilla volumization using vestibular incision subperiosteal tunneling access technique in esthetic rehabilitation - Santhosh B Shenoy; Vinaya Bhat; Parvathi B Kottakkunnummal; Shahira; Chethan Hegde; Biju Thomas (Wolters Kluwer Medknow Publications, 2020)
An accurate diagnostic and interdisciplinary approach is essential for obtaining suitable, conservative, and predictable results in areas with high esthetic demand. Patients reporting with an improper prosthesis that has a black triangle pose a challenge for soft-tissue esthetic rehabilitation. Re-restoration of such cases with conventional fixed prosthesis would be undesirable due to imbalance in pink and white esthetics. This case report describes an interdisciplinary approach to maintain the existing midline diastema and correction of black triangle in the interproximal area between abutment and pontic in the esthetic zone. Minimally invasive vestibular incision subperiosteal tunneling access technique with connective tissue graft was planned for reconstructing the interdental papilla, followed by prosthetic rehabilitation of edentulous site with fixed partial denture using loop connector design to maintain the midline diastema. Postoperative result showed a comprehensive, pink and white rehabilitation to meet the patient's esthetic demand.